Vitronectin-based hydrogels recapitulate neuroblastoma growth conditions - Monferrer, Ezequiel; Dobre, Oana; Trujillo, Sara; González Oliva, Mariana Azevedo; Trubert-Paneli, Alexandre; Acevedo-León, Delia; Noguera, Rosa; Salmeron-Sanchez, Manuel (Frontiers in Cell and Developmental Biology, 2022)
The tumor microenvironment plays an important role in cancer development and the use of 3D in vitro systems that decouple different elements of this microenvironment is critical for the study of cancer progression. In neuroblastoma (NB), vitronectin (VN), an extracellular matrix protein, has been linked to poor prognosis and appears as a promising therapeutic target. Here, we developed hydrogels that incorporate VN into 3D polyethylene glycol (PEG) hydrogel networks to recapitulate the native NB microenvironment. The stiffness of the VN/PEG hydrogels was modulated to be comparable to the in vivo values reported for NB tissue samples. We used SK-N-BE(2) NB cells to demonstrate that PEGylated VN promotes cell adhesion as the native protein does. Furthermore, the PEGylation of VN allows its crosslinking into the hydrogel network, providing VN retention within the hydrogels that support viable cells in 3D. Confocal imaging and ELISA assays indicate that cells secrete VN also in the hydrogels and continue to reorganize their 3D environment. Overall, the 3D VN-based PEG hydrogels recapitulate the complexity of the native tumor extracellular matrix, showing that VN-cell interaction plays a key role in NB aggressiveness, and that VN could potentially be targeted in preclinical drug studies performed on the presented hydrogels.